Integrating Oral Health at a Free Medical Program - Bannon, Annika; Silk, Hugh (Journal of Student-Run Clinics, 2019)
Free medical clinics offer crucial access to primary care services for underinsured and uninsured patients. Most patients served by these clinics lack dental coverage. Oral health is an important part of overall health, but few free clinics currently offer basic preventive oral health care like fluoride varnish and dental hygiene education. The purpose of this article is to describe the process of integrating oral health services into an existing free medical clinic, discuss challenges and elements of success, and convey hopes for the clinic’s future.